Peran Guru Sekolah Minggu dalam Mengembangkan Kemampuan Berpikir Kritis pada Anak Usia 11-12 Tahun - Evalina Chrisna Damanik; Lusia Rahajeng; Manat Siahaan; Rondo Alvirano Morihito Victoria Salomo; Desi Sianipar (Sekolah Tinggi Alkitab Jember, 2023)
Critical thinking is one of the potentials of a child and needs to be developed. In Sunday School, teachers must play a role in developing critical thinking skills in children, especially for children aged 11-12 years. Therefore, this study aims to generate ideas about the role of Sunday School teachers in developing critical thinking skills in children aged 11-12 years. This study uses qualitative research methods through a literature study approach. The results of this study are Sunday School teachers can do several things to develop children's critical thinking skills, namely understanding the concept of Biblical theology about critical thinking, imitating Jesus as the Great Teacher in critical thinking, and guiding children in critical thinking. Sunday School teachers must understand each child with their thinking abilities; provide teaching materials that stimulate children to think critically; provide a variety of learning methods; provide opportunities for children to search for their learning materials; and encourage children to express their thoughts creatively and usefully. Keyword: The role of Sunday School teacher, critical thinking, children aged 11–12 year.